Co-regulation of innate and adaptive immune responses induced by ID93+GLA-SE vaccination in humans - Fiore-Gartland, Andrew; Srivastava, Himangi; Seese, Aaron; Day, Tracey; Penn-Nicholson, Adam; Luabeya, Angelique Kany Kany; Du Plessis, Nelita; Loxton, Andre G.; Bekker, Linda-Gail; Diacon, Andreas; Walzl, Gerhard; Sagawa, Zachary K.; et al. (Frontiers in Immunology, 2024)
Development of an effective vaccine against tuberculosis is a critical step towards reducing the global burden of disease. A therapeutic vaccine might also reduce the high rate of TB recurrence and help address the challenges of drug-resistant strains. ID93+GLA-SE is a candidate subunit vaccine that will soon be evaluated in a phase 2b efficacy trial for prevention of recurrent TB among patients undergoing TB treatment. ID93+GLA-SE vaccination was shown to elicit robust CD4+ T cell and IgG antibody responses among recently treated TB patients in the TBVPX-203 Phase 2a study (NCT02465216), but the mechanisms underlying these responses are not well understood. In this study we used specimens from TBVPX-203 participants to describe the changes in peripheral blood gene expression that occur after ID93+GLA-SE vaccination. Analyses revealed several distinct modules of co-varying genes that were either up-or down-regulated after vaccination, including genes associated with innate immune pathways at 3 days post-vaccination and genes associated with lymphocyte expansion and B cell activation at 7 days post-vaccination. Notably, the regulation of these gene modules was affected by the dose schedule and by participant sex, and early innate gene signatures were correlated with the ID93-specific CD4+ T cell response. The results provide insight into the complex interplay of the innate and adaptive arms of the immune system in developing responses to vaccination with ID93+GLA-SE and demonstrate how dosing and schedule can affect vaccine responses.